Training for generalization in Theory of Mind: a study with older adults - Cavallini, Elena; Bianco, Federica; Bottiroli, Sara; Rosi, Alessia; Vecchi, Tomaso; Lecce, Serena (Frontiers in Psychology, 2015)
Theory of Mind (ToM) refers to the ability to attribute independent mental states to self and others in order to explain and predict social behavior. Recent research in this area has shown a decline in ToM abilities associated with normal aging that is of a moderate magnitude or greater. Very few studies have investigated whether it is possible to improve older adults’ ToM abilities. The present study was designed to address this gap in the literature by evaluating the impact of a ToM training on practiced and transfer tasks. We provided older adults with a variety of activities designed to facilitate the generalization of benefits to other ToM-demanding tasks. Participants were 63 healthy older adults, native Italian speakers (Mage = 71.44, SD = 5.24, age range: 63-81 years). Participants were randomly assigned to one of two groups: the ToM training (age range: 63-81 years) and the physical-conversation training (age range: 64-81 years). Training effects were measured using the Strange Stories (practiced task) and the Animation task (transfer task). Results revealed the efficacy of the training in producing improvements on practiced but also on transfer tasks.